Dietetic interns’ perception on inclusion of spirituality in dietetic counselling - Wan Mohd Yusri, Wan Nur Syifa'; Mamat, Nik Mazlan (2018)
Emerging evidence suggest that it is time to examine whether future healthcare professionals are learning to address religious or spiritual issues in discipline-appropriate ways. Current research suggests that health outcomes are positively related to patients’ religious or spiritual beliefs. As such, discussing spirituality issues with patient may become an area of interest among dietetics intern as well as dietitian. The aim of the present study is to explore the perception and readiness of dietetics interns undergoing clinical practice, in discussing spirituality issues during counselling session with patients.